Propulsive force symmetry generated during butterfly swimming Simetria da força propulsiva gerada pelas mãos durante o nado borboleta - Pereira G.S.* (2015)
© 2015, Universidade Federal de Santa Catarina. All right reserved.The aim of the study was to analyze the hand force symmetry in butterfly swimming. Fourteen male and female swimmers (18.4 ± 4.9 years old, 71.8 ± 14.6 kg of body mass, 1.78 ± 0.09 m of height and mean performance that corresponds to 74.9 ± 5.8% of the world record). Subjects performed three trials of 25 m of butterfly swimming at maximal speed. Mean and maximum forces were estimated for each hand using pressure sensors of the Aquanex System (Swimming Technology Research, USA). The comparisons between force values for dominant and non-dominant hands were made through Student’s T test for dependent samples (p<0.05). In addition, the symmetry Index (SI) was calculated as a relative measure of the force applied by each hand. The mean and maximum force for the dominant hand corresponded, respectively, to 55.7 ± 14.7 N and 114.7 ± 39.6 N. For the non-dominant hand, values were 51.2 ± 14.7 N for mean force and 110.7 ± 36.7 N for maximum force. Significant differences were found between dominant and non-dominant hands for both variables (p<0.01). The symmetry index analysis showed mean values of 8.9% for mean force and of 12.6% for maximum force, and most swimmers presented values higher than 10% for mean and/or maximum forces. Further studies should be performed in order to investigate the relationship between hand force symmetry and swimming performance.